2005
DOI: 10.1007/s11183-005-0015-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetically modified organisms and risks of their introduction

Abstract: The major goal of this review is to assess food risks of the introduction of genetically modified (GM) crops. The author analyzes the properties of the several classes of target proteins used in the transgenic constructions and discusses the problems that arise due to the pleiotropic action of transgenic proteins, the horizontal transfer of the transgenic constructions, primarily in bacteria, and their instability. Particular consideration is given to elevated risks of using the GM plant varieties for producin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 98 publications
0
11
0
2
Order By: Relevance
“…Numerous reports on this topic have been published in the past with the conclusions on the lack of any harmful effects on animal and human health (2,3,5,6,14,19), however, opposite opinions also exist and are experimentally documented (9,15). Public concerns raised above all the possible impact of GM crops on the environment and food safety.…”
mentioning
confidence: 99%
“…Numerous reports on this topic have been published in the past with the conclusions on the lack of any harmful effects on animal and human health (2,3,5,6,14,19), however, opposite opinions also exist and are experimentally documented (9,15). Public concerns raised above all the possible impact of GM crops on the environment and food safety.…”
mentioning
confidence: 99%
“…Dispersion and deposition of maize pollen depend on the intensity of pollen being shed during flowering as well as on the meteorological and environmental conditions, the topography, soil conditions, the texture of leaves, and the feeding behaviour of NTOs like caterpillars (Lang et al 2004;VdI 4330 Part 13, 2010 . 2008;Kulikov 2005;Singh et al 2006;Gathmann et al 2006, Sparrow 2010. A model exercise by Perry et al (2010) suggested that adverse effects of Bt-maize pollen drift may be negligible on three lepidopteran species.…”
mentioning
confidence: 99%
“…Indirect effects on L. terrestris are more probable since the transgenes produce no toxic substances, which aim on lumbricids. The randomly insertion of a transgene into the genome of a host plant may change plant metabolism via undesired effects on other host genes or their regulation, for example, resulting in an altered C/N ratio, lignin content or secondary metabolite composition in the host plant (Ioset et al, 2007;Kulikov, 2005). These so-called pleiotropic effects possibly result in a change of the nutritional value and also change palatability and decomposability (Saxena and Stotzky, 2001a;Poerschmann et al, 2005).…”
Section: Introductionmentioning
confidence: 99%